تحديد الخصائص المورفومترية لحوض شط الاعمى في منطقة الشيب شرق محافظة ميسان - الموسوي حسين عذاب; حسن الساعدي محمد وحيد (Journal of College of Education, 2018)
The Shatt Valley is one of the seasonal valleys in the Shib area east of Maysan province. It is located in the study area and is astronomical between the two latitudes 38 ° 31 ° - 9 ° 32 ° North, and the arc length 19.5¯ 47 ° -51 ° 47 ° east. In the east of the province of Maysan bordered by the north of the good and from the south Hor Hweiza, while on the east is bordered by Iran and the west of the Moratorium and the north-west of the Horn of Snaif, and occupies the valley in place of important in terms of hydrological impact in the study area after the basin of the River Dwerig, This is because the eastern region of Maysan is characterized by the absence of permanent rivers through which the land can be invested in Economic activities, especially agricultural and industrial. It was found that the valley in Greene depends on the cyclones and the flow of water in the valley to reach its water to Iraq and its investment, as well as the shape of the basin, which tends to the rectangular shape. This explains the slow arrival of the water wave to the estuary and the basin is characterized by a low numerical density.